Desain Strategi Pencegahan Kontaminasi Silang di Industri Mi Instan - Fahri Rizal Syahid; Lia Amalia; Syahrir Akil; Aji Jumiono; Erna Puspasari; Mardiah Mardiah (Jurnal Ilmiah Pangan Halal, 2026)
The rapid growth of the instant noodle industry increases production complexity and the risk of cross-contamination through raw materials, personnel, equipment, sanitation activities, and shared production areas. This study aimed to identify internal and external factors affecting cross-contamination prevention and to determine priority strategies for an instant noodle company. The research was conducted through literature review, company document analysis, field observation, and expert judgment involving production, quality assurance/quality control, and warehouse personnel selected by purposive sampling. Internal and external conditions were evaluated using SWOT, Internal Factor Evaluation, External Factor Evaluation, and Internal-External matrices, while strategy priorities were determined using Fuzzy Analytical Hierarchy Process. The IFE and EFE scores were 2.636 and 2.929, respectively, placing the company in quadrant V, which indicates a hold and maintain position. Fuzzy AHP results showed that the main strategic priorities were strengthening food safety and halal certification systems through standard operating procedures, audits, and traceability; optimizing production space to support export regulatory compliance; and improving hygiene infrastructure through epoxy flooring, deep cleaning, and ATP-based verification. These strategies may strengthen cross-functional control and reduce cross-contamination risk in instant noodle production.